PERTUMBUHAN SAWI HIJAU (Brassica juncea L.) PADA MEDIA DENGAN PEMBERIAN KOMPOS CAMPURAN LIMBAH BLOTONG, AMPAS TEBU, DAN GULMA PAITAN (Tithonia diversifolia) - Purwaningsih, Ch. Endang (Widya Warta, 2021)
This study aimed to assess the growth of mustard greens (Brassica juncea L.) in the compost-treated soil growing medium in the form of a mixture of filter mud and bagasse, with paitan (Tithonia diversifolia) weed. The research was conducted with a completely randomized design (CRD) with 7 treatments, each with 3 replications, namely: K1: control, 3 kg of lean soil without fertilizer; B1: soil with 25% bagasse and paitan compost; B2: soil with 50% bagasse and paitan compost; B3: soil with 75% bagasse and paitan compost; C1: soil with 25% filter mud and paitan compost; C2: soil with 50% filter mud and paitan compost; C3: soil with 75% filter mud and paitan compost. Planted in a polybag in a greenhouse. Growth parameters included plant height, number of leaves, and leaf area, while the productivity parameter is fresh plant weight. The results showed that the mustard greens plant in treatment B1 produced the best growth in the number of leaves (14.67 leaves), total leaf area (2389.00 cm2), and fresh plant weight (319.33 g). While the best plant height was found in B3 treatment (38.33 cm).